The first record of Postia ptychogaster (Polyporales, Fomitopsidaceae) in Ukraine (CHORNOMORSKI BOTANICAL JOURNAL, 2018)
The mycological researches of aphyllophoroid fungi completed at Ichnia National Nature Park (Ichnia district, Chernihiv Region, Ukraine) resulted in discovering Postia ptychogaster, which is a new polypore species for mycobiota of Ukraine. This species was found at different stages of development on fallen branches of Picea abies, which is the most favorable substrate for the species development. This species inherent feature is ability to form the anamorphic stage, preceding development of the teleomorphic stage. Such phenomenon is rather unusual for the species of Polyporales. The macro- and micromorphological features were provided for the study specimen, both of the anamorphic and the teleomorphic stages, with the original photos and figures thereof attached. We have also discussed the ecological peculiarities and the general distribution of P. ptychogaster in the world. We have found out that cenooptimum of this species is located within the coniferous forests zone. This assumption is supported by the fact that this species is the most common in the Northern European countries. In the Central Europe this species occurs less often, where all over the Southern European countries it has been record in Italy only. Most likely, in the mixed forests zone P. ptychogaster is located on the eastern boundary of this species natural area. We managed to find it in the Forest Steppe. Whereas, Ichnia national nature park is located on the northern part of the Forest Steppe, immediately adjacent to the mixed forests zone, probably, the substrate necessary for P. ptychogaster development was available there. Presumably, the foregoing species can be also found in the other districts in the mixed forests zone and in the northern Forest Steppe of Ukraine. However, new specimens should be search for to prove this assumption.
Keywords: polypores, anamorphic stage, Ichnia National Nature Park.